2016
DOI: 10.1017/s2040174416000167
|View full text |Cite
|
Sign up to set email alerts
|

The establishment of DOHaD working groups in Australia and New Zealand

Abstract: The evidence underpinning the developmental origins of health and disease (DOHaD) is overwhelming. As the emphasis shifts more towards interventions and the translational strategies for disease prevention, it is important to capitalize on collaboration and knowledge sharing to maximize opportunities for discovery and replication. DOHaD meetings are facilitating this interaction. However, strategies to perpetuate focussed discussions and collaborations around and between conferences are more likely to facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…These efforts may support better health for the next generation(s) and reduce future health inequities. 12,15,57,58,61,68 Nonetheless, previous work has identified a number of areas where translating DOHaD knowledge has the potential to cause social, psychological or even physical harm. [21][22][23][24][25] These concerns include: placing undue emphasis and thus stress and blame on expecting mothers; marginalizing or minimizing the roles of pregnant women's main supports; and, finally, taking emphasis away from the structural and policy-based factors shaping children's environments during development.…”
Section: Potential (Unintended) Consequences Of Direct-to-public Dohamentioning
confidence: 99%
See 3 more Smart Citations
“…These efforts may support better health for the next generation(s) and reduce future health inequities. 12,15,57,58,61,68 Nonetheless, previous work has identified a number of areas where translating DOHaD knowledge has the potential to cause social, psychological or even physical harm. [21][22][23][24][25] These concerns include: placing undue emphasis and thus stress and blame on expecting mothers; marginalizing or minimizing the roles of pregnant women's main supports; and, finally, taking emphasis away from the structural and policy-based factors shaping children's environments during development.…”
Section: Potential (Unintended) Consequences Of Direct-to-public Dohamentioning
confidence: 99%
“…Specifically, Australia is working with New Zealand to assemble a joint working group on DOHaD 'Translation, Policy, and Communication', mainly comprising DOHaD-focused researchers interested in KT. 57 This group seeks to synthesize evidence related to the DOHaD hypothesis and to deliver 'a consistent message' to various stakeholders and to the general public via as many different media and interpersonal forums as possible. 57 Importantly, this group intends to relay simple messages such as ones 'explaining the basic principles of DOHaD' and to listen carefully to public responses to this kind of messaging.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The concept of the developmental origin of health and disease has been put forward to expand the hypothesis of the foetal origins of adult diseases. This concept states that exposing the foetus to a suboptimal environment may lead to an individual being increasingly susceptible to developing diseases in adulthood . Experimental studies have identified a critical window, where the foetus is susceptible to alcohol intake in the period prior to implantation, which may contribute to chronic disease outcomes.…”
Section: Epigenetic Effectsmentioning
confidence: 99%